Association of MRI Measures With Disease Severity and Progression in Progressive Supranuclear Palsy - Picillo, Marina; Abate, Filomena; Ponticorvo, Sara; Tepedino, Maria Francesca; Erro, Roberto; Frosini, Daniela; Del Prete, Eleonora; Cecchi, Paolo; Cosottini, Mirco; Ceravolo, Roberto; Salle, Gianfranco Di; Salle, Francesco Di; et al. (Frontiers in Neurology, 2020)
Objective: To verify the association of midbrain-based MRI measures as well as cortical volumes with disease core features and progression in patients with Progressive Supranuclear Palsy (PSP). Methods: Sixty-seven patients (52.2% with Richardson’s syndrome) were included in the present analysis. Available midbrain-based MRI morphometric assessments as well as cortical lobar volumes were computed. Ocular, gait and postural involvement at the time of MRI was evaluated with the PSP rating scale. Specific milestones or death were used to estimate disease progression up to 72 months follow up. Hierarchical regression models and survival analysis were used for analyzing cross-sectional and longitudinal data, respectively. Results: Multivariate models showed vertical supranuclear gaze palsy was associated with smaller midbrain area (OR:0.02, 95%CI 0.00 to 0.175, p = 0.006). Cox regression adjusted for age, disease duration and phenotype demonstrated that lower midbrain area (HR:0.122, 95%CI 0.030 to 0.493, p=0.003) and diameter (HR:0.313, 95%CI 0.112 to 0.878, p=0.027), higher MR Parkinsonism Index (HR:6.162, 95% CI 1.790 to 21.209, p=0.004) and larger third ventricle width (HR:2.755, 95%CI 1.068 to 7.108, p=0.036) were associated with higher risk of dependency on wheelchair. Conclusions: Irrespective of disease features and other MRI parameters, reduced midbrain size is significantly associated with greater ocular motor dysfunction at the time of MRI and more rapid disease progression over follow up. This is the first comprehensive study to systematically assess the association of available midbrain-based MRI measures and cortical volumes with disease severity and progression in a large cohort of patients with PSP in a real-world setting.